Pembaharuan Hukum Tata Negara Dalam Dinamika Politik Hukum - Kuswan Hadji; Nur Azizah; Nur Shabrina; Irma Firnanda; Nian Puspita; Annisa Hafida (Jurnal Hukum dan Sosial Politik, 2024)
As legal politics is used as a fundamental guideline in the process of identifying values, establishing, shaping and developing national law in Indonesia, it plays a significant role in the formation of Indonesian legislation and national law. Given the relationship between Constitutional Law and the development of society, it is clear that understanding Constitutional Law involves not only the study of the Constitution, but should also focus more on the occurrence of the Constitution itself. In this context, it is very important to do renewal and awareness in thinking in the field of Constitutional Law. To maintain its dynamic nature, Constitutional Law considers both formal and functional viewpoints. The role of legal politics in achieving state goals is the basic policy of state governance that will be, is, and is legal according to the law with the goals to be achieved by the state are goals that are in line with current legal policies, which can change and are closely related to legal policies and the direction of national development